A Tractable Drosophila Cell System Enables Rapid Identification of Acinetobacter baumannii Host Factors - Qin, Qing-Ming; Pei, Jianwu; Gomez, Gabriel; Rice-Ficht, Allison; Ficht, Thomas A.; de Figueiredo, Paul (Frontiers in Cellular and Infection Microbiology, 2020)
Acinetobacter baumannii is an important causative agent of nosocomial infections worldwide. The pathogen also readily acquires resistance to antibiotics, and pan-resistant strains have been reported. A. baumannii is widely regarded as an extracellular bacterial pathogen. However, accumulating evidence demonstrates that the pathogen can invade, survive or persist in infected mammalian cells. Unfortunately, the molecular mechanisms controlling these processes remain poorly understood. Here, we show that Drosophila S2 cells provide several attractive advantages as a model system for investigating the intracellular lifestyle of the pathogen, including susceptibility to bacterial intracellular replication and limited infection-induced host cell death. We also show that the Drosophila system can be used to rapidly identify host factors, including MAP kinase proteins, which confer susceptibility to intracellular parasitism. Finally, analysis of the Drosophila system suggested that host proteins that regulate organelle biogenesis and membrane trafficking contribute to regulating the intracellular lifestyle of the pathogen. Taken together, these findings establish a novel model system for elucidating interactions between A. baumannii and host cells, define new factors that regulate bacterial invasion or intracellular persistence, and identify subcellular compartments in host cells that interact with the pathogen.